A statistical study of the effect of manufacturing methods on the mechanical properties of high-density polyethylene/layered double hydroxide composites - Inglis, Helen M. (University of Pretoria, 2023)
Thesis (PhD (Mechanical Engineering))--University of Pretoria, 2023.